Asurvey on automatic music generation - Jain, Shubham; Pandian, A (International Journal of Engineering and Technology, 2018)
Just like you should not watch a foreign language movie without its subtitles, identically you should not listen to music without its lyrics Music lyrics are words that combine to produce a song in harmony. Usually the music lyrics that we normally listen to are human written and no machine involvement is present. Writing music has never been a easy task, lot of challenges are involved in this because the music lyrics need to be meaningful and at the same time it needs to be in harmony and sync with the music being played over it . They are written by great artist who have been writing music lyrics for years. This project tries to automate the process of music lyrics generation using computer program which we produce lyrics and reduce the burden on human skills and can generate new music lyrics and a very faster rate than humans ever can. This project also aims toward the merge of human and artificial intelligence.